The complete book of breastfeeding - Olds, Sally Wendkos; Marks, Laura; Eiger, Marvin S. (New York : Workman Pub., 2010)
Provides information about nutrition and exercise, explains how lactation works, and offers advice to working mothers about breastfeeding.
Includes bibliographical references and index.
Keywords: Breastfeeding; Mothers -- Health and hygiene; Breast feeding; Mothers -- Health and hygiene